Theoretical Study on Stereodynamics of $H + NeH^+ (v=0, j=0) → NeH^ +H$ Reaction (Journal of Atomic and Molecular Sciences, 2016)
The stereodynamics of reaction $H + NeH^+ (v=0, j=0) → H + NeH^+$ is studiedon a new potential energy surface (PES) constructed by Lü et al., using the quasiclassicaltrajectory (QCT) method. The influence of collision energy for the reaction $H+ NeH^+ (v=0, j=0) → H + NeH^+$ has been studied. The distributions of $P(θ_r),$ $P(φ_r)$ and PDDCSs have been calculated at four different collision energies. It can be foundthat the product rotational angular momentum $j'$ aligned along the y-axis. Moreover,the product rotational angular momentum vector $j'$ is preferentially oriented along thepositive direction of y-axis at low collision energy, but preferentially oriented along thenegative direction of y-axis at high collision energy. The results indicate the collisionenergy plays an important part in the stereodynamics of the title reaction.
Keywords: vector correlation; QCT method; polarization; alignment; exchange reaction.